Nutritional Status And Quality Of Food In Childeen Under Five Years Of Age In Benin (International Journal of Scientific Research and Management (IJSRM), 2023)
Background Malnutrition is a public health problem in developing countries. The aim of our work is to assess the nutritional status and dietary quality of children under 5 years of age. Objective This study focused on children seen in the pediatric department of the Saint Martin de Papanè Hospital during the period from April 6 to July 6, 2021. It is a descriptive and analytical survey by questionnaire on 208 children aged 0 to 59 months. Results The evaluation of the nutritional status of these children under 5 years of age is predominantly male (sex ratio 1.2) and the analysis of the answers to the questions asked of their respective mothers has made it possible to better appreciate the nutritional situation of the children in this study area and to identify the determinants associated with this malnutrition. The study revealed that 74.88% of children are stunted, 90.34% suffer from global acute malnutrition and 79.43% are underweight. Exclusive breastfeeding is very rare, with only 11% of children between the ages of 0 and 6 months receiving only breast milk. The evaluation of dietary diversity reveals that 76.92% of children have a low dietary diversity. In fact, 86% of the children surveyed receive an inadequate complementary diet based on cereals and 67.31% are subjected to the family dish that is poor in nutrients. 59% of the homes in which the children live are more than 5 km from the health centers, 56.73% of the children’s mothers have no education and 25% have a low level of education. Conclusion According to our results, poor weaning practices, diseases, sibling rank and low level of education of mothers are the associated determinants of malnutrition observed in the study population in this area of northeast Benin.